2017
DOI: 10.1063/1.4971490
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach to obtaining JWL parameters from cylinder tests

Abstract: Abstract. An analytical method for determining parameters for the JWL Equation of State from cylinder test data is described. This method is applied to four datasets obtained from two 20.3 mm diameter EDC37 cylinder tests. The calculated pressurerelative volume (p-V r ) curves agree with those produced by hydro-code modelling. The average calculated Chapman-Jouguet (CJ) pressure is 38.6 GPa, compared to the model value of 38.3 GPa; the CJ relative volume is 0.729 for both. The analytical pressure-relative volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Jackson [2] showed that not accounting for it would incur a 2-3% error in velocity magnitude for a cylinder test with an ideal explosive; the error magnitude generally increases for explosives with slower detonation velocities but high product energies. Full reconstruction of the cylinder motion and subsequent product isentrope determination continues to generate interest from other researchers [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Jackson [2] showed that not accounting for it would incur a 2-3% error in velocity magnitude for a cylinder test with an ideal explosive; the error magnitude generally increases for explosives with slower detonation velocities but high product energies. Full reconstruction of the cylinder motion and subsequent product isentrope determination continues to generate interest from other researchers [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For ignition and growth modelling, the equation of state of the unreacted explosives and the reaction products is required. A Jones-Wilkins-Lee (JWL) equation of state is always applied for the unreacted explosives and the reaction products as Equations 2 and 3, respectively [17][18][19]:…”
Section: Ignition and Growth Modellingmentioning
confidence: 99%
“…The pressure obtained using equation 1 is shown as a function of relative volume [1] in Fig.4 a), also shown is the fit to it using the standard Jones-Wilkins-Lee (JWL) equation of state. This fit yields a Chapman-Jouguet pressure of 38.6 GPa which compares well to the accepted hydrocode value of 38.3 GPa.…”
Section: Lifmentioning
confidence: 99%
“…The results of the cylinder test can then be used to obtain the pressure-volume relationship for the expanding detonation products; this can be done directly [1][2][3][4] as is the case in this work or indirectly using hydrocodes [5,6]. In addition to the usually measured wall expansion and VoD the temperature of the detonating products was also measured.…”
Section: Introductionmentioning
confidence: 99%